From theory to practice: the contributions of Psychopedagogy in the teaching of History (Research, Society and Development, 2020)
This article aims to raise theoretical and practical reflections and propose changes in the history teaching process, seeking foundations in the field of psychopedagogy, to assist within the action of educating, raising discussions about changes in the classroom within the discipline of History . We base the discussions presented in this article on the conceptions of Ramos and Scoz on psychopedagogy, as a theoretical approach that can contribute to the process of teaching and learning history. And we rely on authors such as Portela, Schmidt, Netto & Costa and others to support reflections on the teaching of history. Methodologically we adopt the assumptions of bibliographic research. In the findings of this research we realized that there is a need to rethink about the methodologies of teaching in the current, in order to make it more dynamic and effective. In this sense, the use of a tool that seeks to assist the teacher in class has been increasingly necessary. Among these tools, playfulness and the use of material and immaterial teaching resources stand out, all of this, in the quest to make the History an increasingly constructive and meaningful discipline inside and outside the school environment.